A Biomimetic Nickel Complex with a Reduced CO2 Ligand Generated by Formate Deprotonation and Its Behaviour towards CO2. Issue 24 (15th May 2018) - Zimmermann, Philipp; Hoof, Santina; Braun‐Cula, Beatrice; Herwig, Christian; Limberg, Christian
Abstract: Reduced CO2 species are key intermediates in a variety of natural and synthetic processes. In the majority of systems, however, they elude isolation or characterisation owing to high reactivity or limited accessibility (heterogeneous systems), and their formulations thus often remain uncertain or are based on calculations only. We herein report on a Ni−CO2 2− complex that is unique in many ways. While its structural and electronic features help understand the CO2 ‐bound state in Ni, Fe carbon monoxide dehydrogenases, its reactivity sheds light on how CO2 can be converted into CO/CO3 2− by nickel complexes. In addition, the complex was generated by a rare example of formate β‐deprotonation, a mechanistic step relevant to the nickel‐catalysed conversion of H x CO y z − at electrodes and formate oxidation in formate dehydrogenases. Abstract : A distinct formate : β‐Deprotonation of a nickel formate complex with strong bases provides a side entrance for the generation of reduced CO2 species. The obtained Ni−CO2 2− complex resembles the intermediates found within the CO dehydrogenase and in synthetic systems for CO2 reduction. By varying the base, proton‐coupled electron transfer can be induced, which enables the intermolecular formation of C−C coupling products.